Dual-coil magnetomotive optical coherence tomography for contrast enhancement in liquids - Kim, Jongsik (Optical Society of America, 2013)
Magnetomotive optical coherence tomography (MM-OCT) is a functional extension of OCT which utilizes magnetically responsive materials that are modulated by an external magnetic field for contrast enhancement and for elastography to assess the structural and viscoelastic properties of the surrounding tissues. Traditionally, magnetomotive contrast relies on the interaction between the displacement of magnetic particles induced by an external magnetic field and the micro-environmental restoring (elastic) force acting on the particles. When the restoring force from a sample containing magnetic particles is weak or non-existent, the MM-OCT signal-to-noise ratio (SNR) can degrade significantly. We have developed a novel solenoid configuration to enable MM-OCT imaging in samples that do not have an elastic restoring force, such as liquids. This coil configuration may potentially enable real-time MM-OCT imaging.